The Effect of Unsaturated Polyester Resin from Recycled PET as Compatibilizer for Styrene-Butadiene (SBR)/Acrylonitrile-Butadiene (NBR) Rubber Blend: Effect of UPR on Rubber Blends - Akhter, Tehzeeb; Raza, Nudrat Zahid; Mahmood, Khalid; Iqbal, Mahmood (Biological Sciences - PJSIR, 2009)
Unsaturated polyester resin (UPR) from recycled PET flakes was prepared by depolymerization with propylene glycol and polyesterified with adipic acid. The effect of addition of 5, 10 and 15 phr of unsaturated polyester resin (UPR) on the compatibility and physicomechanical properties of styrene-butadiene rubber (SBR) and acrylonitrile-butadiene rubber (NBR) blends were studied. DSC, TGA, MDR, FTIR and chemical methods were used to determine the degree of compatibility. The mechanical and physical properties of the blends were found to improve with addition of 10 phr UPR for SBR/NBR blend.